2022
DOI: 10.1371/journal.pone.0265820
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 antibodies in febrile patients from an endemic region of dengue and chikungunya in Peru

Abstract: Introduction The rapid expansion of the novel SARS-CoV-2 virus has raised serious public health concerns due to the possibility of misdiagnosis in regions where arboviral diseases are endemic. We performed the first study in northern Peru to describe the detection of SARS-CoV-2 IgM antibodies in febrile patients with a suspected diagnosis of dengue and chikungunya fever. Materials and methods A consecutive cross-sectional study was performed in febrile patients attending primary healthcare centers from April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The samples in this study were collected while the COVID-19 pandemic was still ongoing in the country. Studies that were conducted in countries endemic to Chikungunya show that CHIKV continued to circulate and cause disease during the COVID-19 pandemic [15] with possible coinfections [16]. Despite the relatively low incidence of COVID-19 in Jambi during the month in which this study was conducted, the mobility restrictions as a measure of COVID-19 transmission control that are still implemented in cities, including Jambi, create difficulties in other disease surveillance during a pandemic.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The samples in this study were collected while the COVID-19 pandemic was still ongoing in the country. Studies that were conducted in countries endemic to Chikungunya show that CHIKV continued to circulate and cause disease during the COVID-19 pandemic [15] with possible coinfections [16]. Despite the relatively low incidence of COVID-19 in Jambi during the month in which this study was conducted, the mobility restrictions as a measure of COVID-19 transmission control that are still implemented in cities, including Jambi, create difficulties in other disease surveillance during a pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…The samples in this study were collected while the COVID-19 pandemic was still ongoing in the country. Studies that were conducted in countries endemic to Chikungunya show that CHIKV continued to circulate and cause disease during the COVID-19 pandemic [15] with possible coinfections [16]. Despite the relatively low in-…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, more patients were tested positive for SARS-CoV-2 than for dengue virus, which concurs with our findings. 66 Perhaps, healthcare professionals should pay more attention to AFI cases while considering the possibility of SARS-CoV-2. Despite the perplexity of clinical manifestations of the viruses and falsepositive/cross-reaction associated with them, symptoms, such as anosmia, dysgeusia, diarrhea and cough, were specific to COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that when individuals are quarantined, they experience loneliness, anger, posttraumatic stress and confusion 69 . These feelings escalate as a result of paranoia associated with the infection, the period of quarantine, frustration, boredom and stigmatization 66 …”
Section: Discussionmentioning
confidence: 99%
“…The mobility restriction during pandemic has affected the health-seeking behaviour of people [11]. Similar studies that were conducted in countries endemic to Chikungunya show that CHIKV continued to circulate and cause disease during the COVID-19 pandemic [12] with possible coinfections [13]. Due to the lack of specific clinical presentation for CHIKV infection, efficient and accurate diagnostic methods are necessary for the proper management [14,15].…”
Section: -2019 2018-2019 2020-2021mentioning
confidence: 99%